Scientific Opinion on the substantiation of a health claim related to vitamin D and contribution to normal bone and tooth development pursuant to Article 14 of Regulation (EC) No 1924/2006 - EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) (EFSA journal, 2014)
Following an application from Specialised Nutrition Europe (formerly IDACE), submitted pursuant to Article 14 of Regulation (EC) No 1924/2006 via the Competent Authority of France, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to vitamin D and contribution to normal development of bones and teeth. The food constituent, vitamin D, which is the subject of the health claim, is sufficiently characterised. Contribution to normal development of bones and teeth is a beneficial physiological effect for infants and young children. A claim on vitamin D and maintenance of normal bones and teeth in the general population has already been assessed with a favourable outcome. The Panel considers that the role of vitamin D in bone and tooth mineralisation and homeostasis applies to all ages, including infants and young children (from birth to three years). The Panel concludes that a cause and effect relationship has been established between the dietary intake of vitamin D and contribution to normal development of bones and teeth.